1988
DOI: 10.1254/jjp.48.473
|View full text |Cite
|
Sign up to set email alerts
|

N-Demethylation of Methyl and Dimethyl Derivatives of Phenytoin and Their Anticonvulsant Activities in Mice

Abstract: Abstract-Anticonvulsant activities of 3-methylphenytoin (3-MP) and 1 ,3 dimethylphenytoin (1,3-DMP) were observed to peak 3 hr after i .p. administration of the drugs dissolved in dimethylsulphoxide (DMSO), while maximal activity was obtained within 15 min with phenytoin. HPLC was employed to monitor the plasma concentrations of all three compounds at various time intervals after injecting 3-MP or 1,3-DMP. In both cases, phenytoin appeared in the plasma, gradually reaching 14-15 /ag/ml in 3 hr. The time course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…It is also known to decrease the seizure threshold and act as a proconvulsant [29]. In our study, we found an improvement in learning and memory in the passive avoidance apparatus and the Morris water maze apparatus after 30% DMSO coupled with a decrease in seizure latency when compared with DMSO pretreatment.…”
Section: Discussionsupporting
confidence: 64%
“…It is also known to decrease the seizure threshold and act as a proconvulsant [29]. In our study, we found an improvement in learning and memory in the passive avoidance apparatus and the Morris water maze apparatus after 30% DMSO coupled with a decrease in seizure latency when compared with DMSO pretreatment.…”
Section: Discussionsupporting
confidence: 64%
“…However, it was demonstrated that DMSO may enhance the proconvulsant activity of the dissolved drugs because DMSO may lower seizure threshold (Wong et al, 1988). Similarly, the antiepileptic effect of i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in general, the structure−activity relationship studies of anticonvulsants revealed the need for the retention of at least one hydrophobic site and H-bond donors/acceptors together with certain relative orientation between these features to exhibit anticonvulsant activity. 5a-g The hydantoin nucleus and the phenyl ring in phenylmethylenehydantoin (PMH) provided the basic structural requirement for activity. Previous studies from our laboratory have demonstrated a weak maximal electroshock seizure (MES) response for the unsubstituted PMH . Thus, the main objective of the present study is to investigate the influence of substitutions in the phenyl ring of PMH on its anticonvulsant activity.…”
Section: Introductionmentioning
confidence: 97%